Activation of the Adipose Tissue NLRP3 Inflammasome Pathway in Cancer Cachexia - Jesus, Joyce de Cassia Rosa de; Murari, Ariene Soares de Pinho; Radloff, Katrin; Moraes, Ruan Carlos Macêdo de; Figuerêdo, Raquel Galvão; Pessoa, Ana Flavia Marçal; Rosa-Neto, José César; Matos-Neto, Emídio Marques; Alcântara, Paulo S. M.; Tokeshi, Flavio; Maximiano, Linda Ferreira; Bin, Fang Chia; et al. (Frontiers in Immunology, 2021)
Background: Cachexia is a paraneoplastic syndrome that accompanies and compromises cancer treatment, especially in advanced stages, affecting the metabolism of several organs. The adipose tissue is the first to respond to the tumor, contributing to the secretion of inflammatory factors, perhaps in an attempt to restore homeostasis. Low-grade and sustained inflammation is considered a particularity of cancer cachexia, responsible for its clinical consequences. Inflammation is a defensive innate response and the NLRP3 inflammasome is a multiprotein complex involved in caspase-1 activation and the processing of the cytokines IL-1 and IL-18. Aim: based on the evidence from a study with animals, we proposed to verify the activation of the NLRP3 inflammasome pathway in two adipose tissue depots in patients with colorectal cancer Results: In the CC group, some genes had decreased expression in ScAT and increased in PtAT (TLR4, Caspase-1) or increased in ScAT and decreased in PtAT (NF-𝜅B p50, NF-𝜅B p65, IL-1β); other genes, such as CD36, showed lower expression, while NLRP3 and IL-18 mRNA expression were higher in both tissues. Caspase-1 basal protein levels in the ScAT culture supernatant were higher in WSC and CC when compared to the CTL group. Basal ScAT explant culture IL-1β and IL-18 protein content in ScAT supernatant were decreased in the WSC and CC group. Conclusions: The results demonstrate heterogeneous adipose tissue responses in oncologic cachexia and may serve as targets for future therapeutic strategies to modulate this pathway.